ANALYSIS OF G+22 BUILDING BY USING SHEAR WALLS IN VARIOUS LOCATIONS UNDER INFLUENCE OF SEISMIC LOAD BY USING ETABS - Bhagawat, Ganesh; Mohite, Dnyaneshwar B. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The behavior of high-rise reinforced concrete (RCC) structures during earthquakes is strongly influenced by the placement of shear walls, which serve as primary lateral load-resisting elements. This research aims to investigate the impact of shear wall positioning on the seismic performance of a G+22 commercial building and to identify the most efficient configuration for achieving stability, safety, and economy. A detailed three-dimensional model of the building was developed and analyzed in ETABS software. The seismic response was evaluated using the Response Spectrum Method in compliance with IS 1893:2016 provisions. Three shear wall arrangements were considered for comparison: (i) corner positions, (ii) middle outer positions, and (iii) inner/core positions. The building’s response was assessed in terms of story drift, lateral displacement, base shear, and story stiffness. The analysis reveals that shear walls located at the inner/core region of the building deliver superior performance compared to corner and middle-outer placements. The core configuration effectively minimizes lateral displacements and inter-story drifts, while also enhancing stiffness and overall stability under seismic loading. Although other arrangements contribute to resistance, they are less efficient in controlling deformations and ensuring uniform load distribution. The findings highlight that the inner/core positioning of shear walls provides the best structural efficiency for high-rise RCC buildings subjected to seismic forces. This configuration not only improves serviceability by reducing drift but also enhances the overall seismic resilience of the structure. The study underscores the importance of strategic shear wall placement in tall building design and offers practical guidance for engineers and designers in achieving safe, durable, and economical structural systems.